2008
DOI: 10.1007/s00128-008-9420-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil Dissipation and Leaching Behavior of a Neonicotinoid Insecticide Thiamethoxam

Abstract: Persistence and leaching of thiamethoxam in soil were studied under laboratory conditions. The persistence studies carried out at two fortification levels and under three moisture regimes revealed that thiamethoxam persisted beyond 90 days in all the treatments with half-life varying from 46.3 to 301.0 days. Under dry conditions, the dissipation was faster at 10 mg kg(-1) level as compared to 1 mg kg(-1), whereas the reverse trend was observed under field capacity moisture and submerged conditions. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 16 publications
(12 reference statements)
7
72
0
1
Order By: Relevance
“…Highly significant R 2 values indicated that the dissipation of thiamethoxam conformed to the first order kinetics. Soil factors like availability of soil moisture (Gupta 2008), organic carbon content and pH (Karmakar 2006) play an important role in dissipation of pesticides from soil. However, since soil moisture content in the present investigation was maintained to near field capacity so availability of moisture might not be the sole reason for the observed faster dissipation of thiamethoxaam in silty clay loam as compared to loam.…”
Section: Resultsmentioning
confidence: 99%
“…Highly significant R 2 values indicated that the dissipation of thiamethoxam conformed to the first order kinetics. Soil factors like availability of soil moisture (Gupta 2008), organic carbon content and pH (Karmakar 2006) play an important role in dissipation of pesticides from soil. However, since soil moisture content in the present investigation was maintained to near field capacity so availability of moisture might not be the sole reason for the observed faster dissipation of thiamethoxaam in silty clay loam as compared to loam.…”
Section: Resultsmentioning
confidence: 99%
“…This has favored the use of the systemic pesticide thiamethoxam, which can be persistent in soil for 90 days, in addition it degrades and percola itself settling in groundwater in which it is highly soluble (4.95 X 10 -11 ha 25° C). Its hydrolytic degradation is in a range of pH of 5 to 9, reason why it is necessary to carry out studies of dissipation and motility in water, as well as learning how to handle and apply it in papaya crops, since producers use it due to its systemic and contact activity, that becomes suitable for an efficient control of sucking insects such as aphids [21,13]. Producers from the study area of the municipality of Cotaxtla, have mentioned that mite has caused severe damage to papaya agroecosystems ( Table 1).…”
Section: IIImentioning
confidence: 99%
“…The half-life of imidacloprid in soil was 48-90 days, depending on the ground cover (Scholz & Spiteller, 1992). Laboratory experiments showed that persistence of another neonicotinoid, thiamethoxam is highly depending on moisture and the half-life varied from 45 to 300 days (Gupta et al 2008). The half-life of neonicotinoids increases with increasing soil colloids.…”
Section: Neonicotinoidsmentioning
confidence: 99%